Effects of speed, gender, and visual wheel modifications on time-to-arrival judgments of cyclists - Millar, Sarah-Kate; Noël, Benjamin; Geisen, Mai; Rein, Robert; Klatt, Stefanie (Frontiers in Future Transportation, 2025)
Current evidence suggests that the speed of an object influences its time-to-arrival (TTA) estimation; in particular, greater speeds are associated with more inaccurate TTA estimates, which yield higher-risk decisions about approaching persons or objects. This study aims to investigate the impacts of bike speed and additional factors like bike type and gender of the cyclist on TTA estimates in a naturalistic cycling setting. Two experiments were performed to examine the influences of speed on TTA estimations with conventional pedelecs and e-bikes. The results indicate that a combination of factors (experiment 1) involving cyclist gender, cycle speed, and only the arrival distance of the bike at the point of decision making (experiment 2) affect the accuracy of TTA estimation. However, the inclusion of additional information on the cycle speed (based on paint on the front wheel) has no positive (experiment 1) or negative (experiment 2) influence on the evaluation.